Gem-diaurated gold(III) complexes: synthesis, structure, aurophilic interaction, and catalytic activity - Wunsch, Jonas; Eberle, Lukas; Mullen, Joseph P.; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Inorganic chemistry, 2022)
We present a protocol to synthesize air stable gem-diaurated gold(III) compounds from 1,3-diketones in a single cycloauration step with tetrachloroauric acid. So far related species were only accessible from phosphonium bis(ylide) ligands which hold the two gold atoms in close proximity. Lacking such a constraint, our compounds show the longest Au-Au distances of all gem-diaurated carbons, ranging from 3.26 to 3.32 Å. Modeling based on results of CCSD(T) calculations shows no stabilization by aurophilic interactions for our gold(III) systems, compared to 9.1 kcal/mol for gold(I) gem-diauration. This demonstrates no aurophilic interactions are needed for the isolation of air stable gem-diaurated gold(III) complexes. We show the new gem-diaurated gold(III) compounds are active in the gold-catalyzed phenol synthesis and highly active in the cycloisomerization of an N-propargylcarboxamide; here, we obtained the so far highest known TON of over 2500 per gold atom with respect to the oxazole formation.
Gesehen am 05.07.2022